Morphological Image Analysis of Transmission Systems - Radhakrishnan, P.; Sagar, B.S.D.; Venkatesh, B. (2005)
This paper proposes morphological decimation of power network images for the purpose of analysis. The method creates a graphical image of a power network with a thickness of lines proportional to their respective rated megavolt-ampere capacity. Through morphological tools, the network image is decimated. This decimation process eliminates weak lines. Thus, strongly connected subnetworks emerge. This method of identification of several strongly connected subnetworks in a large network is tested on an IEEE test system. The method provides a quick bird's eye view of the strong subnetworks in a power system. Creation and decimation of network images to analyze other facets of the transmission system are also presented and discussed.